solve for y: xy-wy = t

I got an answer myself, im not sure if this is rite, its y= -(t/w-xy/w)

mrlevan3 Aug 29, 2017

edited by
Guest
Aug 29, 2017

#1**+2 **

Well, in xy-wy = t, you know that xy and wy both have y in them. (Yeah, that's not really a good explanation -_-)

So you can make that into: y(x-w) = t. Because if you distribute y to (x-w), the result is the same as the original.

Now, we have y(x-w) = t.

We need to isolate y to solve for y.

So divided both sides by (x-w) to isolate y.

you get y = t/(x-w)

And that's the answer.

Correct me if I am wrong.

Gh0sty15 Aug 29, 2017

#1**+2 **

Best Answer

Well, in xy-wy = t, you know that xy and wy both have y in them. (Yeah, that's not really a good explanation -_-)

So you can make that into: y(x-w) = t. Because if you distribute y to (x-w), the result is the same as the original.

Now, we have y(x-w) = t.

We need to isolate y to solve for y.

So divided both sides by (x-w) to isolate y.

you get y = t/(x-w)

And that's the answer.

Correct me if I am wrong.

Gh0sty15 Aug 29, 2017